2011
DOI: 10.1016/j.ymgme.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

An open-label Phase I/II clinical trial of pyrimethamine for the treatment of patients affected with chronic GM2 gangliosidosis (Tay–Sachs or Sandhoff variants)

Abstract: Late-onset GM2 gangliosidosis is an autosomal recessive, neurodegenerative, lysosomal storage disease, caused by deficiency of ß-hexosaminidase A (Hex A), resulting from mutations in the HEXA (Tay-Sachs variant) or the HEXB (Sandhoff variant) genes. The enzyme deficiency in many patients with juvenile or adult onset forms of the disease results from the production of an unstable protein, which becomes targeted for premature degradation by the quality control system of the smooth endoplasmic reticulum and is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 20 publications
3
49
0
Order By: Relevance
“…1f) 19 as an inhibitor of the wild-type enzyme. Pyrimethamine chaperones disease-causing mutant proteins in cells and has since entered phase I and II trials for treatment of GM2 gangliosidosis 34 . In addition to class selectivity, one complication encountered in the development of glycoside hydrolase chaperones is that dosing in trials must be tuned to favor chaperoning over inhibition.…”
Section: Review Articlementioning
confidence: 99%
“…1f) 19 as an inhibitor of the wild-type enzyme. Pyrimethamine chaperones disease-causing mutant proteins in cells and has since entered phase I and II trials for treatment of GM2 gangliosidosis 34 . In addition to class selectivity, one complication encountered in the development of glycoside hydrolase chaperones is that dosing in trials must be tuned to favor chaperoning over inhibition.…”
Section: Review Articlementioning
confidence: 99%
“…As it is the case in many lysosomal diseases, the severity and onset of G M2 gangliosidosis inversely correlates with the residual rate of G M2 catabolism. Specifically, in infantile Tay-Sachs and Sandhoff patients the residual G M2 conversion rate does not exceed 0.5%, in juvenile and adult forms it reaches 2–4% of normal, while the residual rates above about 10% of normal seem to be compatible with the healthy state [32], [33]. Interestingly, the three recently reported patients homozygous for p.P55L in GM2AP presented with a neurological movement disease without ocular features and an onset at the age of 7–8 years [9].…”
Section: Discussionmentioning
confidence: 95%
“…3 The observed increase in Hex A activity levels in patients' leukocytes (up to a maximum of 4-fold) was closely correlated with their plasma levels of PYR, which varied according to the oral dose of the drug (25, 50, 75, or 100 mg/ day) and the metabolism of each patient; i.e., patients taking the same dose could have very different levels of plasma PYR. As an anti-malarial, PYR has 1000-fold higher affinity for the parasite versus human DHFR.…”
Section: ■ Introductionmentioning
confidence: 82%
“…2 Indeed, we have shown that, in some late-onset forms of GM2 gangliosidosis (Tay-Sachs and Sandhoff diseases), the Hex A activity in patient fibroblasts can be enhanced by 2−3-fold. 3 Recently it has been reported that treating Dutch APP E693Q mice (a mouse model of Alzheimer's disease) with a PC for Hex dramatically reduced the accumulation of a β-amyloid peptide:ganglioside (GM2 and GM3) complex. This reduction was associated with improved learning behavior and decreased anxiety in the treated mice.…”
Section: ■ Introductionmentioning
confidence: 99%